TRANFORMASI DIGITAL SISTEM TILANG ELEKTRONIK DALAM UPAYA PENGEMBANGAN SMART CITY DI KOTA PALEMBANG - Febrianza, Muhammad; Marleni; Mahriadi, Nopriawan (Universitas Bina Taruna Gorontalo, 2024)
This study aims to examine the extent to which the effectiveness of the implementation of the electronic ticketing system is enforced by the vision factor and the variables applied and what factors influence the success and obstacles. Transformation of the digital electronic ticketing system in an effort to develop a smart city in the city of Palembang. The research analysis uses Edward III's theory, namely: standard operating procedures, resources, communication and disposition which are the attitudes of the Palembang Police Traffic Unit. The study uses a qualitative descriptive approach method, data collection techniques, observation interviews, documentation, data collection was carried out on the Palembang Police TMC staff. The results of the study showed the awareness of drivers in traffic order, the lack of Palembang Police TMC personnel, drivers are still looking for loopholes in the ETLE system by covering vehicle plate numbers, making fake plate numbers, the number of vehicle ownership using the name of the old owner, and the delivery of ticket letters that have not been on target because drivers have moved domicile. The need for additional TMC staff personnel, community communication to need to be improved again to build more concrete socialization, the implementation of ETLE can be emphasized again to the community in order to create support for conducive socio-cultural conditions and improve ETLE technology that makes no loopholes for traffic violators for the realization of the smart city of Palembang, the world's destination.